2020
DOI: 10.1002/chem.202003875
|View full text |Cite
|
Sign up to set email alerts
|

Assessing The Key Photophysical Properties of Triangulenium Dyes for DNA Binding by Alteration of the Fluorescent Core

Abstract: Four‐stranded G‐quadruplex (G4) DNA is a non‐canonical DNA topology that has been proposed to form in cells and play key roles in how the genome is read and used by the cellular machinery. Previously, a fluorescent triangulenium probe (DAOTA‐M2) was used to visualise G4s in cellulo, thanks to its distinct fluorescence lifetimes when bound to different DNA topologies. Herein, the library of available triangulenium probes is expanded to explore how modifications to the fluorescent core of the molecule affect its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Moreover, this chemosensor and derivatives thereof have the potential to be applied for the fluorimetric detection of pH gradients and extracellular nucleic acids in biofilms, [31] that have been suggested just recently to contain G4‐DNA as functional component [60] . Although numerous fluorescent probes for G4‐DNA are known, [9–19] to the best of our knowledge, no examples have been reported so far with these particular features. Namely, only a few fluorescent probes for G4‐DNA have been reported that operate at lower pH, [61] but these probes do not exhibit the dual‐mode response of compound 3 a .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, this chemosensor and derivatives thereof have the potential to be applied for the fluorimetric detection of pH gradients and extracellular nucleic acids in biofilms, [31] that have been suggested just recently to contain G4‐DNA as functional component [60] . Although numerous fluorescent probes for G4‐DNA are known, [9–19] to the best of our knowledge, no examples have been reported so far with these particular features. Namely, only a few fluorescent probes for G4‐DNA have been reported that operate at lower pH, [61] but these probes do not exhibit the dual‐mode response of compound 3 a .…”
Section: Discussionmentioning
confidence: 99%
“…For an efficient detection, however, either the emission intensity of the otherwise non‐fluorescent ligand has to increase strongly or the emission energy has to shift distinctly. Thus, several organic fluorophores have been introduced that serve this purpose, for example benzimidazole, [9] benzindole, [10] triazine, [11] coumarin, [12] cyanine, [13] pyridinium, [14,15] quinolinium, [15,16] quinolizinium, [15,17] triangulenium [18] and benzothiazole [19] based dyes. Among the promising compound classes for this application are also DNA‐binding natural products with suitable fluorescence properties, because these compounds usually provide sufficient affinity, and often selectivity, towards DNA, along with the required biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It displayed emission enhancement upon DNA binding, which was attributed primarily to deaggregation. 57 …”
Section: Perylenoidsmentioning
confidence: 99%
“…In this study we aim at widening the chemical diversity and tuning the optical and redox properties of ADOTA + and DAOTA + dyes by investigating chlorination, specifically targeting positions of the ADOTA + , DAOTA + and DMQA + chromophores not previously investigated. Tuning of the redox properties has become particularly interesting due to the high interest in applications of ADOTA + , DAOTA + and DMQA + in photo induced electron transfer (PET) based sensors [20][21][22][23] , photo catalysts, [7][8][9][24][25] redox agents, 26 and in electroluminescent systems. [27][28] Specifically, we here report the synthesis, and optical and redox properties of 1-chloro-DAOTA + (1), 9,11dichloro-DAOTA + (2) and 5,7-dichloro-ADOTA + (3) (Figure 2).…”
Section: Introductionmentioning
confidence: 99%